A demonstration of the Borg centiMax® Scale (CR100) for performance evaluation in diving. Issue 3 (3rd July 2018) - Borg, Elisabet; Love, Chantella
Abstract: In many sports, for example in diving, figure skating, or ski jumping, judges subjectively score the performance on a category scale. The level-anchored ratio Borg centiMax® Scale (CR100), a general intensity scale from 0 to 100 commonly used for self-appraisal of exertion, is an interesting and valuable alternative. The aim was to explore the possibility of using the Borg centiMax® Scale (CR100), for performance evaluation in diving. In Study 1, 16 participants used the centiMax scale and the traditional diving scale (FINA) during a judicial training course on pre-recorded material; and in Study 2, six professional judges used the two scales during qualifying, semi-finals, and finals in the Swedish Championships in Örebro, 2012. Strong and significant correlations were obtained between judged performances with the two scales ( r ≥ .8), as well as with contest results ( r ≥ .6). The continuous and finely graded centiMax scale has promising possibilities of improving measurement with both level determinations (how good) and ratio relationships (how much better). With a Borg CR scale, more interesting comparisons can be made, for example, direct comparisons between performance measures and perceptual variables (e.g., perceived exertion and motivation). This is of importance in training and coaching of athletes.